Kappa-carrageenan as immunostimulant to control infectious myonecrosis (IMN) disease in white shrimp Litopenaeus vannamei - Dian Febriani; . Sukenda; Sri Nuryati (Jurnal Akuakultur Indonesia)
ABSTRACT